Modelling loans to non-financial corporations in the euro area - Christoffer Kok; David Marqués-Ibá\~nez; Carlotta Rossi (European Central Bank (ECB), 2009)
We model the determinants of loans to non-financial corporations in the euro area. Using the Johansen (1992) methodology, we identify three cointegrating relationships. These relationships are interpreted as the long-run loan demand, investment and loan supply equations. The short-run dynamics of loan demand for the euro area are subsequently modelled by means of a Vector Error Correction Model (VECM). We perform a number of specification tests, which suggest that developments in loans to non-financial corporations in the euro area can be reasonably explained by the model. We then use the estimated model to analyse the impact of permanent and temporary shocks to the policy rate on bank lending to nonfinancial corporations.
Keywords: C32; C51; 330; bank credit; cointegration; error-correction model; euro area; non-financial corporations; Kreditgeschäft; Unternehmensfinanzierung; Kointegration; Kointegration; Eurozone